Thermal tolerance and critical maxima examined in marine gastropods inhabiting around Karachi Nuclear Power Plant - Shaikh, Wajiha; Panhwar, Sher Khan; Yaqoob, Nadeem (Frontiers in Marine Science, 2022)
Bensthic communities along the coastal basins are an indication of ecosystem health but highly susceptible owing to manmade activities. This study envisages thermal tolerance in sea snails Monodonta canalifera, Nerita albicilla and Tylothais savignyi inhabiting around the outfall and intake structures of Karachi Nuclear Power Plant (KANUPP). To test the adaptability and vulnerability, a lethality test protocol under controlled temperature was applied in the laboratory where they were exposed at 25, 30, 35, and 40°C, which was raised to 45°C after an acclimation period of 1 week. The critical thermal maximum (CTmax) for the three species was found to be between 39 and 42°C, whereas the lethal temperature (LT50) tests revealed that at the utmost 45°C was lethal for M. canalifera. The correlation between LT50 and CTmaxima (R = 0.47, p = 0.00) and LT50 and body sizes reveals that the thermal adaptability in N. albicilla and T. savignyi (R = 0.65, p = 0.00) was relatively higher than that at 45°C given in the laboratory. In addition, microscopic changes due to temperature, which appeared in the foot (adhesive part) of each species, were deduced from the histological examination. The outcomes of this study would help to underline the ecosystem health around KANUPP and highlight precautionary measures required for the newly established K2/K3 power units to safeguard habitat.